2007
DOI: 10.1007/s11207-007-0402-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Traveling Waves in Filament Threads

Abstract: High-resolution Hα filtergrams (0.2 ) obtained with the Swedish 1-m Solar Telescope resolve numerous very thin, thread-like structures in solar filaments. The threads are believed to represent thin magnetic flux tubes that must be longer than the observable threads. We report on evidence for small-amplitude (1 -2 km s −1 ) waves propagating along a number of threads with an average phase velocity of 12 km s −1 and a wavelength of 4 . The oscillatory period of individual threads vary from 3 to 9 minutes. Tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
173
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(181 citation statements)
references
References 18 publications
5
173
3
Order By: Relevance
“…Recent observations of Alfvénic transverse waves in spicules have been reported by, e.g, De Pontieu et al (2007), Zaqarashvili et al (2007), Kim et al (2008), He et al (2009a,b), Okamoto & De Pontieu (2011). In addition, propagating transverse waves in thin threads of solar prominences have been observed (e.g., Lin et al 2007Lin et al , 2009) and Alfvénic waves in bright points have been reported (Jess et al 2009). The role and implications of the observed Alfvénic waves for the heating of the solar atmosphere have been discussed by, e.g., Erdélyi & Fedun (2007); De Pontieu et al (2007); McIntosh et al (2011);Cargill & De Moortel (2011).…”
Section: Introductionmentioning
confidence: 90%
“…Recent observations of Alfvénic transverse waves in spicules have been reported by, e.g, De Pontieu et al (2007), Zaqarashvili et al (2007), Kim et al (2008), He et al (2009a,b), Okamoto & De Pontieu (2011). In addition, propagating transverse waves in thin threads of solar prominences have been observed (e.g., Lin et al 2007Lin et al , 2009) and Alfvénic waves in bright points have been reported (Jess et al 2009). The role and implications of the observed Alfvénic waves for the heating of the solar atmosphere have been discussed by, e.g., Erdélyi & Fedun (2007); De Pontieu et al (2007); McIntosh et al (2011);Cargill & De Moortel (2011).…”
Section: Introductionmentioning
confidence: 90%
“…For instance, observations of filaments made by Lin et al (2005a,b) suggest that the thickness of thin threads forming the filaments is ≤ 250 km, that only a small portion of filament threads are filled with cool plasma, and that this absorbing plasma is continuously flowing along the thread structure with velocities 15 ± 10 km s −1 . Lin (2004) Lin et al (2007) have found evidence for traveling waves in the threaded structure of a filament and, in some cases it seems that the propagating waves move in the same direction as mass flows. They also have determined the wavelength of a propagating wave, obtaining a value of around 3,000 km.…”
Section: Referencementioning
confidence: 99%
“…Small-amplitude magnetohydrodynamic (MHD) waves and oscillations are frequently observed in solar prominence threads Lin et al 2005Lin et al , 2007Lin et al , 2009Mackay et al 2010;Arregui et al 2012). MHD oscillations in prominences are well studied by both slab and tube approximations (Roberts 1991;Joarder & Roberts 1992a, 1992bOliver et al 1993;Joarder et al 1997;Díaz et al 2002Díaz et al , 2005Dymova & Ruderman 2005;Terradas et al 2008;Oliver 2009;Arregui et al 2011Arregui et al , 2012.…”
Section: Introductionmentioning
confidence: 99%